2021
DOI: 10.1016/j.jcte.2021.100270
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in cystic fibrosis

Abstract: Cystic Fibrosis (CF) requires lifetime multidisciplinary care to manage both pulmonary and extra pulmonary manifestations. The median age of survival for people with CF is rising and the number of adults with CF is expected to increase dramatically over the coming years. People with CF have better outcomes when managed in specialty centers, however access can be limited. Telemedicine and technology-based care solutions may help to overcome barriers to availability and improve access. This review outlines the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 114 publications
(129 reference statements)
0
14
0
4
Order By: Relevance
“…In 2021 Desimone et al . conducted a review of telehealth for CF management, and similar to the other reviews, found that while there are many exemplars of telehealth being used within CF care for a variety of indications, there continues to be a lack of data related to health outcomes and the use of telehealth for CF related co-morbidities [9] .…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In 2021 Desimone et al . conducted a review of telehealth for CF management, and similar to the other reviews, found that while there are many exemplars of telehealth being used within CF care for a variety of indications, there continues to be a lack of data related to health outcomes and the use of telehealth for CF related co-morbidities [9] .…”
Section: Introductionmentioning
confidence: 82%
“…This can be seen in the US where the Cystic Fibrosis Learning Network established a TeleHealth Innovation Lab (TH ILab) to support transition from a traditional care model to one that included telehealth [29] . Furthermore, these working groups can provide guidance on other outstanding queries surrounding CF telehealth decision making such as cost, patient/MDT burdens, and barriers to availability [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, DXA scanners are expensive, require technical expertise to operate, and are not available in many clinical centers. Scheduling additional visits with patients for the purpose of body composition assessment may not be feasible due to long travel distances to their clinical care centers or to a facility with a DXA scanner [ 24 ]. An additional concern with DXA is the radiation exposure which, although low-dose, similar to a standard X-ray, and generally considered safe, may pose future health risks with repeated doses [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%